Penggambaran Halusinasi dalam Film Setengah Hari Kurang Sedikit - Andreas Kurnia Sutjiadi; Altobeli Lobodally (UNIVERSITAS KALBIS, 2022)
Hallucinations are things that can basically be seen and observed through one's behaviour. As a reality, hallucinations can be constructed through mass communication products, such as films. The film referred to in this study is a short film entitled Setengah Hari Kurang Sedikit. The aim of this study was to determine the depiction of hallucinations in the Setengah Hari Kurang Sediki films. The theory used in this research is the theory of social reality construction with a constructivism paradigm and a qualitative a pproach. This study uses the semiotic method, and the data analysis technique in this study is to use the Peirce triadic model, where the sign is an amalgamation of representamen, object, and interpretant. Th e result of the research was found that there are four meanings of hallucinations, namely: happiness that occurred in the past, losing loved ones, someone's unpreparedness to lose someone who has a strong relationship with himself, and anxiety.